Globalization, Citizenship and Subjectivity : An Analysis of the Changes in the Last Four Generations - Raut, Sunita (Namuna Academic Journal, 2023)
Globalization is the process of connecting the world without any barrier and boarder. Particularly this process is impacting our society, culture, economy, polity, people’s thought, and everyday life. Globalization incorporates, integrates and diffuses all the human and non-human activities in all over the world without any boarder. Similarly, this process constructs, reconstructs, shapes and reshapes the citizen’s attributes, experiences, ideas, feeling, belief, expectation, perception, thoughts and socio-cultural understanding of the individual relating with respective community. In this article, the author tries to analyze interlink of globalization, citizenship and subjectivity with researcher’s family history and stories of close relatives. And also seeks the answer of the question that how people’s subjectivities have changed over the periods, in one generation to another? Additionally, this study provides insight not only into the author's family, but also into the comparative historical antecedents of Nepali society, and how its own subjectivity was shaped, molded, and influenced by globalization with the state-building and changing process.